Retrospective study on the occurrence of canine lymphoma and associated breed risks in a population of dogs in NSW (2001–2009). Issue 5 (May 2017) - Yau, PPY; Dhand, NK; Thomson, PC; Taylor, RM
Abstract : Objective: To identify risk factors for canine lymphoma in dogs from New South Wales, Australia, and to compare factors affecting remission duration. Methods: Client‐owned dogs diagnosed with lymphoma presented to the University Veterinary Teaching Hospital (UVTH), University of Sydney, between 2001 and 2009 (n = 134) were compared with a control population of dogs seen in that period of time with a diagnosis other than lymphoma to evaluate association of explanatory variables (breed, age and sex) with the outcome (case or control status). Results: The Australian Cattle Dog (odds ratio (OR) = 4.71; 95% confidence interval (Cl) 2.31–9.62; P < 0.001), Doberman (OR = 7.64; 95% Cl 2.87–20.34; P = 0.001) and Rottweiler (OR = 4.52; 95% Cl 2.09–9.73; P = 0.001) had increased odds of lymphoma among dogs attending the UVTH compared with crossbreds. The results suggested that the Border Collie (OR = 3.38; 95% Cl 1.52–7.53; P = 0.008) and Boxer (OR = 3.85; 95% Cl 1.65–8.95; P = 0.006) also have increased odds of lymphoma among the pure‐breed dogs attending the UVTH when compared with crossbred dogs. Conclusions: The results of this study confirmed a breed predilection for lymphoma in dogs, with the Australian Cattle Dog and Doberman having increased odds of lymphoma.